STRATEGI INTERNET MARKETING BAND INDIE PEKANBARU DALAM MEMPROMOSIKAN KARYA MUSIK MELALUI REVERBNATION.COM - Gionovan Ayesha; Rumyeni " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Evolution of independent music begins when some bands got to entry the studio because a conflict interest between the owner of record company with idealism in music of the band itself. Some record company think that the flow of the music can not be enjoyed by the public, don’t have the quality and do not follow mainstream music market. This makes indie musicians chose the internet as a promotional strategy to embrace the market share of his own music at social networking. ReverbNation advantages lie in the field of music as well as the latest music features are audio streaming for free. This study aims to determine strategy indie band marketing on internet with content marketing, mobile marketing, continuous marketing, digital intergrated marketing, and visual marketing in promoting piece of music at ReverbNation.com. This study uses qualitative research methods with the presentation of descriptive analysis. The collection of data obtained based on the fact that occurred in the field through observations, interviews, and documentation. New media theory approach by Livingstone. Informants in this study amounted to 5 by using purposive sampling technique, which consists of musicians indie band Pekanbaru simultaneously active users ReverbNation account. Data were analyzed using analysis interactive model of Miles and Huberman. And testing techniques using the data validity extension of participation and triangulation. From the results of this study found that internet marketing strategies indie band Pekanbaru in promoting piece of music at ReverbNation.com through a variety of indicators including: 1.) Content marketing to upload songs, videos and photos of bands such as documentation during a gigs, selling merchandise, then share location using google maps. 2.) Mobile marketing using a smartphone and access the Internet directly from their gadget so that the campaign carried out more efficiently. 3.) Continuous marketing, informants established communication with visitors of the page to create closeness and respond to criticism for the sake of improvement of quality. 4.) Integrated digital marketing, linking uploads the band to all applications of social media such as twitter, facebook, myspace to reach variety consumers. 5.) Visual marketing, informants create unique designs and creative to create a good impression so as to attract the eyes and ears of consumers first.Keywords : Internet marketing strategy, indie band, ReverbNation